Parametric study on the well-oriented growth of InxAl1-xN nanodots by magnetron sputtering. (1st November 2019) - Zhao, Yang; Wang, Hui; Li, Xinzhong; Li, Jingjie; Shi, Zhifeng; Wu, Guoguang; Zhuang, Shiwei; Yin, Chuanlei; Yang, Fan
Abstract: Inx Al1-x N alloys are expected to have immense potential in optoelectronic device applications. However, the synthesis of high quality Inx Al1-x N alloys still remain a difficulty. Herein, we report the growth of Inx Al1-x N alloys on Al2 O3 substrate by radio-frequency magnetron sputtering. The deposition conditions such as nitrogen concentration, substrate temperature and growth time affect the structural and morphological properties of Inx Al1-x N alloys, which were investigated using X-ray diffraction, scanning electron microscope and X-ray photoelectron spectroscopy. The results showed that the Inx Al1-x N alloys grown at lower nitrogen concentration (20%) and higher substrate temperature (500 °C) exhibited phase separation. It was found that the surface morphology of Inx Al1-x N alloys presented a transition from uniform nanodots to disordered nanoclusters with the substrate temperature increased from room temperature to 500 °C. Finally, well-oriented In0 · 62 Al0 · 38 N nanodots were achieved at a nitrogen concentration of 40%, a substrate temperature of 300 °C, and a growth time of 120 min. It was believed that this research will lay a good foundation for the preparation of high-quality InAlN alloys that can be employed in reliable optoelectronic devices.